The Impact of Jujube Witches’ Broom Phytoplasma on the Community Structure of Endophytes in Jujube - Nian Wang; Mengli Wang; Ziming Jiang; Wenzhe Zhang; Ziyang You; Xueru Zhao; Jia Yao; Chenrui Gong; Assunta Bertaccini; Jidong Li (Microorganisms, 2025)
Evidence from an increasing number of studies indicates that plant endophytic microorganisms play a significant role during biotic and abiotic stress resistance. To date, however, only a handful of studies on endophytes in response to the presence of phytoplasmas have been conducted. The production of jujube (Ziziphus jujuba) is threatened by jujube witches’ broom (JWB) disease, which is associated with the presence of the JWB phytoplasma ‘Candidatus Phytoplasma ziziphi’. To investigate the impact of jujube witches’ broom phytoplasma on the endophyte populations in jujube, high-throughput sequencing was performed in healthy and JWB-infected orchard jujube trees and in vitro jujube shoots. The results showed that the presence of JWB phytoplasma in jujube altered the abundance, diversity, and community structure of endophytic bacteria and fungi. In the branches and the roots, the presence of JWB phytoplasma was associated with an increase in the richness of the endophytic communities and a decrease in their diversity, with the phyla Proteobacteria, Firmicutes, and Bacteroidota and the genus ‘Ca. Phytoplasma’ becoming the most abundant. The presence of phytoplasmas was also associated with the remodeling of the endophytic microorganisms’ interaction network, shifting to a simpler biodiversity state. These results demonstrate the response of the jujube endophytic community to the presence of JWB phytoplasmas and shed light on the possible antagonistic agents that could be further evaluated for JWB disease biocontrol.